Neuromarketing in Fast Food: A View About Attention and Intention - Systematic Literature Review (European Journal of Marketing and Economics, 2026)
Neuromarketing, as a multidisciplinary approach, is relevant in the fast-food sector, characterised by quick decision-making and intense competition. The studies analysed demonstrate that sensory and contextual stimuli, such as packaging, nutritional labelling, point-of-sale lighting, and menu design, significantly influence attention, emotion, perceived value, and purchase intention. Studies indicate that sensory and contextual stimuli, such as packaging, nutritional labelling, lighting, and menu design, influence attention, emotion, perceived value, and purchase intention. Tools such as eye tracking, EEG, GSR/EDA, and neuroimaging techniques allow implicit processes and unconscious responses undetected by traditional methods to be captured. Despite knowledge of decision-making, a gap persists between the decision and the actual purchase. It is concluded that the ethical and rigorous use of neuromarketing can enhance the effectiveness of marketing strategies in the fast-food industry.
Keywords: neuromarketing; fast food; FMCG; purchase intention; consumer behaviour